A NOTE ON EXTENDED DISTRIBUTION RECORDS OF RADIOSPONGILLA CEREBELLATA (BOWERBANK, 1863) AND CORVOSPONGILLA ULTIMA (ANNANDALE, 1910) IN MAHARASHTRA, INDIA - UNMESH ADKAR,; PAWANJEET CHHABDA,; ANANTA HARKAL,; PALLAVI RAO, (The Bioscan, 2025)
The study provides the records of extended distribution and taxonomic identification of freshwater sponges collected in Ahilyanagar (Formerly Ahmednagar) and the Pune district of Maharashtra, India. The sponge samples were collected and identified using the colony morphology and structural features of spicules and gemmules observed using Light Microscopy and Scanning Electron Microscopy (SEM). The identified sponge samples are Radiospongilla cerebellata (Bowerbank,1863) and Corvospongilla ultima (Annandale,1910). We provide descriptive notes on their colony morphology and SEM images of gemmules, gemmuloscleres, and spicules. There is a need for further research to obtain a more comprehensive understanding of freshwater sponge taxonomy.